2007
DOI: 10.1016/j.annemergmed.2007.06.306
|View full text |Cite
|
Sign up to set email alerts
|

367: Emergency Medicine Residency Applicants’ Perceptions About Being Contacted After Interview Day

Abstract: ObjectiveWe sought to characterize the experiences and preferences of applicants to emergency medicine (EM) residency programs about being contacted by programs after their interview day but before the rank list submission deadline.MethodsThis cross-sectional study surveyed all applicants to an academic EM residency during the 2006–2007 interview cycle. Participation was anonymous and voluntary. We used a Web-based survey software program to administer the survey in February 2007, after rank lists were submitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…4 However, there remains evidence of interview behavior that violates the spirit of the Match and of ongoing gamesmanship in the postinterview period, with a number of applicants reporting exposure to interview questions about other interview locations, 5 rank preferences, marital status, and plans to have children, [6][7][8] and discomfort when programs contact them following the interview. 9 Besides adding a statement explicitly reminding programs that applicants should not be asked about other interviews, the NRMP does not appear to have adopted any specific policy changes or interventions in response to these data. 5 In this context, we hypothesized that (1) the behaviors continue to take place across a variety of specialties; (2) the behaviors cause distress; and (3) postinterview communication is an aspect of the Match process in which the applicant may prefer change.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, there remains evidence of interview behavior that violates the spirit of the Match and of ongoing gamesmanship in the postinterview period, with a number of applicants reporting exposure to interview questions about other interview locations, 5 rank preferences, marital status, and plans to have children, [6][7][8] and discomfort when programs contact them following the interview. 9 Besides adding a statement explicitly reminding programs that applicants should not be asked about other interviews, the NRMP does not appear to have adopted any specific policy changes or interventions in response to these data. 5 In this context, we hypothesized that (1) the behaviors continue to take place across a variety of specialties; (2) the behaviors cause distress; and (3) postinterview communication is an aspect of the Match process in which the applicant may prefer change.…”
Section: Introductionmentioning
confidence: 99%
“…3 One cross-sectional study of emergency medicine applicants found that 51% changed their rank lists based on post-interview communication. 4 recently, an online thread on Reddit entitled "How to Game the Match. Rank List Tips!"…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 Previous work has shown that most applicants were contacted in some form by programs and that they were glad to receive such communication. 8 Despite the absence of any clear evidence in favor of the practice, medical students applying to EM residency are usually advised by clerkship directors and faculty mentors to communicate their thanks to programs. 9 However, it is currently unknown whether the practice benefits applicants or programs.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%